ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATERI ALJABAR SISWA KELAS VIII SMP NEGERI 2 BANGIL - Desy Permatasari, Bunga Ayu; Setiawan, Toto' Bara; Kristiana, Arika Indah (Kadikma, 2015)
Abstract: This research aims to describe the difficulties experienced by the eighth grade students of SMPN 2 Bangil in solving algebra material problems based on the concept understanding ability and to describe the factors causing the students’ difficulties in learning algebra. The subject of this research is the students of VIIIC and VIIID of SMPN 2 Bangil in the 2013-2014 academic years. The data of the research are obtained from validation sheet, written test, and questionnaire and interview techniques. The results of this study indicate that the students still have difficulties in understanding the concept of algebra, in which the highest difficulty is on the indicator in restating a concept and applying the concept and algorithm into problem solving, while the factors causing the students’ difficulties in learning algebra based on the results of the questionnaire are the internal factor and the external factor. Key words: learning difficulties, the concept understanding ability, algebra.